Progress in Positron Annihilation : Selected Papers from Proceeding of the 39th Polish Seminar on Positron Annihilation (PSPA-10), 20-25 June 2010, Kazimierz Dolny, Poland (Materials science forum ;, 2010)
The aim of this special collection is to present recent progress made, and reflect current ideas, in research fields where positron and positronium are involved. The contents cover a wide range of positron-related research topics; including both fundamental (theoretical calculations, radiation chemistry, hyperfine interactions, positronium physics and chemistry) and applied (metal, polymer, thin film and other materials, development of experimental techniques) aspects. This will be of especial interest to anyone planning to use such techniques. Review from Book News Inc.: This collection of thirty-four papers on nuclear physics, originally delivered at the thirty-ninth Polish Seminar on Positron Annihilation held in Kazimierz Dolny, Poland in June 2010, showcases current research, theory and experimentation in electron-positron annihilation. The papers are divided into four sections examining theoretical calculations, positron annihilation, positronium, and experimental methods and individually discuss such topics as gamma spectrum calculation, the effects of super-strong magnetic fields, localization of positronium in polymers, positron annihilation in under-cooled water and ice and precise measurement of hyperfine splitting of positronium using the Zeeman effect. Contributors include Polish and international particle physicists from a variety of universities and research institutions.